Determinan Cakupan Imunisasi Dasar Lengkap Sebagai Bagian Upaya Pencegahan Stunting Di Kota Medan: Studi Literatur - Syafrina Ulfah; Nurcholisah Fitra (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2025)
Stunting is a chronic nutritional problem characterized by a child’s height being inappropriate for their age, particularly among children under five years old. One of the interventions implemented to prevent stunting is immunization. However, immunization coverage, especially complete basic immunization, has not yet reached the target, including in Medan City. Therefore, this literature study aims to explore the determinants of complete basic immunization coverage in Medan City using the Google Scholar database. The literature search identified nine articles that were extracted and discussed in this study. The determinants of complete basic immunization coverage include individual maternal factors such as age, education level, knowledge, attitudes, and mothers’ beliefs or perceptions toward immunization; social support factors including family support, economic conditions, and prevailing norms and cultural practices within families and communities; as well as health service factors. Comprehensive and integrated interventions are urgently needed to achieve optimal complete basic immunization coverage in Medan City.